Karakteristik Demografi dan Kualitas Hidup Penderita TB Paru di Puskesmas Waingapu, Sumba Timur - Domianus Namuwali (Jurnal Penelitian Kesehatan SUARA FORIKES, 2019)
Pulmonary TB is still a health problem in Indonesia. This disease is associated with poor health conditions, low economic class, unemployment and low education. Every sufferer of pulmonary TB loses time to work around 3-4 months so that it has an impact on the quality of life. The purpose of the study was to analyze the relationship between demographic characteristics and the quality of life of pulmonary TB patients in Waingapu Health Center, East Sumba; with a cross sectional design. The research subjects were selected by total sampling technique. This research was carried out in the Waingapu Puskemas, East Sumba, NTT from August to September 2017. The results of the study showed that the majority of respondents were male (68.75%), aged 25-45 years (50%), elementary education (37.50%) , work (53.12%), good quality of life (93.75%). Based on the results of the Cotingency Coefficient test, there was a relationship between age and sex with the quality of life of patients with pulmonary TB. Furthermore, it is recommended that the Waingapu Health Center provide education for pulmonary TB patients, especially those of productive age to improve their quality of life. Keywords: pulmonary TB, quality of life, demographic characteristics ABSTRAK TB Paru masih merupakan masalah kesehatan di Indonesia. Penyakit ini berhubungan dengan kondisi kesehatan yang buruk, kelas ekonomi yang rendah, pengangguran dan pendidikan yang rendah. Setiap penderita TB Paru kehilangan waktu untuk bekerja sekitar 3-4 bulan sehingga berdampak pada penurunan kualitas hidup. Tujuan dari penelitian adalah menganalisis hubungan karakteristik demografi dengan kualitas hidup penderita TB paru di Puskesmas Waingapu, Sumba Timur; dengan rancangan cross sectional. Subyek penelitian dipilih dengan teknik total sampling. Penelitian ini dilaksanakan di Puskemas Waingapu, Sumba Timur, NTT pada bulan Agustus sampai dengan September 2017. Hasil penelitian menunjukkan bahwa responden terbanyak adalah laki-laki (68.75%), usia 25-45 tahun (50%), pendidikan SD (37.50%), bekerja (53,12%), kualitas hidup baik (93,75%). Berdasarkan hasil uji Cotingency Coefficient didapatkan ada hubungan antara umur dan jenis kelamin dengan kualitas hidup penderita TB Paru. Selanjutnya disarankan agar Puskesmas Waingapu memberikan edukasi pada penderita TB paru, terutama yang berusia produktif untuk meningkatkan kualitas hidup mereka. Kata kunci: TB paru, kualitas hidup, karakteristik demografi